(untitled) (European Journal of Pure and Applied Mathematics, 2009)
The main aim of this paper is to compute Kothe-Toeplitz and null duals of some difference sequence spaces, deï¬ned by means of a ï¬xed equence of multiplier and by an Orlicz function. Further the coincidence for three pairs of analogous spaces is established.